SARS-CoV-2 Antibody Response to Vaccination in Peritoneal Dialysis Patients - Beatriz Donato; Catarina Mateus; Maria Inês Roxo; Carlos Pereira Duarte; Rita Ribeiro Calça; Patrícia João Matias; Patrícia Branco (Publicações Ciência e Vida, 2023)
Introduction: Chronic kidney disease patients have a higher risk of infection and worse clinical outcomes after coronavirus disease. We aimed to assess the prevalence of infection and the humoral response after vaccination in peritoneal dialysis patients. Methods: Three types of vaccines were administered (two doses) with the antibody detection at least six months after. Coronavirus disease 2019 infections, hospital admissions, and deaths were evaluated. Results: From 70 prevalent patients, 45 were included. There was a significant increase in antibody level, with a median of 92 (36, 447) U/mL. Only 4% of patients remained seronegative. History of immunosuppressive therapy was associated with no response (100% vs 60%, p=0.010). There were two infections after the vaccination, without hospital admission. Conclusion: Immunization against coronavirus disease was effective in generating a humoral response in peritoneal dialysis patients. There was also an evident impact of immunosuppressive therapy on vaccine response in peritoneal dialysis patients.